Interpreting biomarker data from the COPHES/DEMOCOPHES twin projects: Using external exposure data to understand biomarker differences among countries - Smolders, R; Den Hond, E; Koppen, G; Govarts, E; Willems, H; Casteleyn, L; Kolossa-Gehring, M; Fiddicke, U; Castaño, A; Koch, H M; Angerer, J; Esteban, M; et al. (Environmental research, 2015)
In 2011 and 2012, the COPHES/DEMOCOPHES twin projects performed the first ever harmonized human biomonitoring survey in 17 European countries. In more than 1800 mother-child pairs, individual lifestyle data were collected and cadmium, cotinine and certain phthalate metabolites were measured in urine. Total mercury was determined in hair samples. While the main goal of the COPHES/DEMOCOPHES twin projects was to develop and test harmonized protocols and procedures, the goal of the current paper is to investigate whether the observed differences in biomarker values among the countries implementing DEMOCOPHES can be interpreted using information from external databases on environmental quality and lifestyle. In general, 13 countries having implemented DEMOCOPHES provided high-quality data from external sources that were relevant for interpretation purposes. However, some data were not available for reporting or were not in line with predefined specifications. Therefore, only part of the external information could be included in the statistical analyses. Nonetheless, there was a highly significant correlation between national levels of fish consumption and mercury in hair, the strength of antismoking legislation was significantly related to urinary cotinine levels, and we were able to show indications that also urinary cadmium levels were associated with environmental quality and food quality. These results again show the potential of biomonitoring data to provide added value for (the evaluation of) evidence-informed policy making.
Keywords: potrava z moře (živočišná); Mercury; Surveys and Questionnaires; Humans; městské obyvatelstvo; kotinin; vlasy, chlupy; External exposure data; dítě; Child; Environmental Monitoring; Female; vystavení vlivu životního prostředí; dospělí; Interpretation; Human biomonitoring; lidé; Biomarkers; Europe; DEMOCOPHES; látky znečišťující životní prostředí; průzkumy a dotazníky; COPHES; Adult; monitorování životního prostředí; venkovské obyvatelstvo; Cadmium; Environmental Pollutants; Hair; biologické markery; ženské pohlaví; vládní regulace; Cotinine; Data Interpretation, Statistical; Seafood; Government Regulation; kadmium; Environmental Exposure; Rural Population; Smoking; kouření; rtuť; Evropa; Urban Population; interpretace statistických dat